ATM and the Mre11-Rad50-Nbs1 complex respond to nucleoside analogue-induced stalled replications forks and contribute to drug resistance - Ewald, Brett (2008)
The Mre11-Rad50-Nbs1 complex and autophosphorylated Ser(1981)-ATM are involved in recognizing and repairing DNA damage, such as double-strand breaks (DSBs). However, the role of these factors in response to stalled replication forks is not clear. Nucleoside analogues are agents that are incorporated into DNA during replication, which cause stalling of replication forks. The molecular mechanisms that sense these events may signal for DNA repair and contribute to survival, but are poorly understood. Cellular responses to both DSBs and stalled replication forks are marked by H2AX phosphorylation on Ser(139) (γ-H2AX), which forms nuclear foci at sites of DNA damage. Here, concentrations of the nucleoside analogues, ara-C, gemcitabine, and troxacitabine, that inhibited DNA synthesis by 90% within 2 h were determined for each agent. Using γ-H2AX as a marker for changes in chromatin structure, we demonstrate that Mre11, Rad50, Nbs1 and phosphorylated ATM respond to nucleoside analogue-induced stalled replication forks by forming nuclear foci that co-localize with γ-H2AX within 2 h. Since neither DSBs nor single-strand breaks were detectable after nucleoside analogue exposure, we conclude that this molecular response is not due to the presence of DNA breaks. Deficiencies in ATM, Mre11, or Rad50 led to a two- to five-fold increase in clonogenic sensitization to gemcitabine, while Nbs1 and H2AX deficiency did not effect reproductive growth. Taken together, these results suggest that ATM, Mre11, and Rad50 are required for survival after replication fork stalling, whereas Nbs1 and H2AX are in-consequential.